Multimodality imaging in cardiac amyloidosis: a primer for cardiologists. (11th May 2020) - Jurcuţ, Ruxandra; Onciul, Sebastian; Adam, Robert; Stan, Claudiu; Coriu, Daniel; Rapezzi, Claudio; Popescu, Bogdan A
Abstract: Amyloidosis is a systemic infiltrative disease, in which unstable proteins misfold, form aggregates and amyloid fibrils which can deposit in various organs: heart, kidneys, liver, gastrointestinal tract, nervous system structures, lungs, or soft tissue. Cardiac amyloidosis (CA) diagnosis requires awareness, high level of clinical suspicion and expertise in integrating clinical, electrocardiographic, and multimodality imaging data. The overall scenario is complex and no single test emerges over the others, but different techniques are useful at various stages of the diagnostic workup. After a clinical suspicion of CA is raised by various non-imaging red-flags, eligible patients should undergo complete echocardiography and multiparametric cardiovascular magnetic resonance imaging. Even though the clinical suspicion of CA is confirmed by cardiac imaging, the accurate differentiation between the two most frequent and treatable amyloid types, i.e. light chain (AL) and transthyretin (ATTR) requires further work-up including phosphate scintigraphy. This article reviews the latest and essential data on multimodality imaging of patients with suspected or confirmed CA in a useful and practical manner for the general and imaging cardiologists.